Pengaruh Kesehatan Mental Karyawan terhadap Kinerja yang Dimediasi oleh Kesejahteraan di Tempat Kerja (Studi Empiris pada Karyawan Divisi Teknologi Informasi di Masa Work From Home) - Dwi Winda Meidina; Netty Laura S. (Universitas Bunda Mulia, 2022)
The implementation of working from home has changed employees' work environment, from an office environment to a home environment. It raises many limitations, like communication and interaction space. It can negatively impact employees because it can trigger irregular working hours and long working hours. IT field is one of the jobs that can be done remotely, but it still have different with the implementation of WFH and pandemic that requires new adaptations. This study aims to determine the effect of innovation culture, self-efficacy on technostress, and technostress, burnout on performance with workplace well-being as a mediating variable for IT employees who work from home. This study uses a survey method with an online questionnaire to 295 IT employees and used as a research sample. Data analysis method used SmartPLS 3.2 program by analyzing the inner and outer models. The results of this study indicate that: innovation culture is significant to technostress, self-efficacy is significant to technostress, innovation culture and technostress is significant to WWB, but burnout to WWB is not significant, technostress, burnout and WWB is significant to performance, WWB can mediate innovation culture and technostress to its effect on performance, WWB is not able to mediate burnout on performance.